Driving Hospital Revisit Intentions Through a Technopreneurship Approach to eWOM Care Quality and Patient Experience - Sianita, Pricillia Priska; Harwani, Yuli; Permana, Dudi; Imaningsih, Erna Sofriana (Pandawan, 2026)
The rapid integration of digital technologies into healthcare services has transformed hospitals into technopreneurial service organizations that actively leverage digital platforms to create value and sustain competitiveness. Electronic Word of Mouth (e-WOM) and patient experience have emerged as critical digital signals shaping patient perceptions and behavioral outcomes. However, empirical evidence explaining the service mechanisms through which these digital factors influence patient loyalty in emerging market healthcare contexts remains limited. This study investigates the influence of e-WOM and patient experience on revisit intention through the sequential mediating roles of care quality and patient satisfaction. A quantitative research design was employed, collecting data from 250 patients of Class B hospitals in Jakarta. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Mediation effects were assessed through bootstrapping with 5,000 resamples. The results demonstrate that e-WOM and patient experience significantly enhance perceived care quality, which subsequently increases patient satisfaction and ultimately strengthens revisit intention. Furthermore, care quality and patient satisfaction jointly function as a sequential dual mediation mechanism. This study contributes to technopreneurship and healthcare management literature by extending traditional patient loyalty models into digitally driven healthcare ecosystems within emerging markets. Practically, the findings highlight the importance of technopreneurial capabilities in managing digital reputation, patient experience design, and service quality innovation to achieve sustainable healthcare performance. The study also supports Sustainable Development Goal 3 (Good Health and Well-being) by emphasizing patient-centered, digitally enabled healthcare delivery.